The Influence of Intellectual Capital on Profitability With Firm Size as an Intervening Variable in Companies Listed on The Jakarta Islamic Index (JII) for The 2016-2022 Period - Ardi Winata; Marlina Widiyanti; Kms. M Husni Thamrin; Isni Adriana; Yuliani Yuliani (Ridwan Institute, 2023)
The purpose of this study is to analyze the direct influence of intellectual capital on profitability in Companies Listed in the Jakarta Islamic Index (JII) for the 2016 – 2022 Period and to analyze the indirect influence of intellectual capital on profitability through firm size in Companies Listed in the Jakarta Islamic Index (JII) for the 2016 – 2022 Period. The population in this study is companies listed in the Jakarta Islamic Index (JII) for the 2016 – 2022 period. The sample of this study was selected by purposive sampling method. There were 11 companies that were used as research samples. The data was analyzed using path analysis operated using Eviews. The results showed that Intellectual capital has an influence and significant on profitability in companies listed in JII for the 2016 – 2022 period. Intellectual capital has a significant influence on firm size, Firm has an influence and significant on profitability and Firm size mediates intellectual capital on profitability in companies listed in JII for the 2016 – 2022 period.